RUMUSAN STRATEGI BISNIS DAN STRATEGI PEMASARAN PADA UMA SAPNA VILLA BERDASARKAN ANALISIS MATRIK IFAS-EFAS - Eugenia Sartini Mega Dewi; Nyoman Candra Tri Wahyuni; Holil Pujiyati; Ni Nyoman Kerti Yasa; I Gst. Ayu Ketut Giantari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Uma Sapna Villa Bali is a company in the hospitality industry, has 26 units with 5 different categories. The company's consumers come from domestic and international tourists. The problem that occurs in this company is the decreased in guest occupancy rates in 2023, where the occupancy rate in 2022 reached 83.50% while in 2023 it decreased to 76.78%. Uma Sapna Villa needs to conduct an analysis of the company's environment both internally and externally using the IE Matrix analysis to determine the business position and formulate strategies as alternative business strategies and their implications for marketing that can be used as recommendations in making policies in the future. The type of research used is descriptive qualitative. Data collection was collected using the Delphi method with in-depth interview techniques guided by questionnaires and observing supporting documents such as the company website and online travel agents. The respondents in this study were 3 top managers from different divisions of Uma Sapna Villa Bali. The data collected was analyzed using the IFAS-EFAS matrix. Based on the results of the IE matrix analysis for the present and future, Uma Sapna Villa Bali is in Quadrant I in the Growth position with a concentration through vertical integration. In this condition, the strategies that can be used are backward integration strategies, market penetration strategies and market development. The implications for marketing strategy are through e-WOM strategies and attractive brand narratives.